Effect of reinforcement particle size on Fe-Cr-AL2O3 Metal Matrix composite - Saidatulakmar Shamsuddin; Shamsul Baharin Jamaludin; Zuhailawati Hussain; Zainal Arifin Ahmad (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.